The role of anticipated emotions in self-control: linking self-control and the anticipatory ability to engage emotions associated with upcoming events - Kruschwitz, Johann D.; Goschke, Thomas; Ahmed Mohamed Ali, Elkhansa; Kraehe, Anne-Carolin; Korb, Franziska Maria; Walter, Henrik (Frontiers in Psychology, 2024)
Self-control is typically attributed to "cold" cognitive control mechanisms that top-down influence "hot" affective impulses or emotions. In this study we tested an alternative view, assuming that self-control also rests on the ability to anticipate emotions directed toward future consequences. Using a behavioral within-subject design including an emotion regulation task measuring the ability to voluntarily engage anticipated emotions towards an upcoming event and a self-control task in which subjects were confronted with a variety of everyday conflict situations, we examined the relationship between self-control and anticipated emotions. We found that those individuals (n=33 healthy individuals from the general population) who were better able to engage anticipated emotions to an upcoming event showed stronger levels of self-control in situations where it was necessary to resist short-term temptations or to endure short-term aversions to achieve long-term goals. This finding suggests that anticipated emotions may play a functional role in self-control-relevant deliberations with respect to possible future consequences and are not only inhibited top-down as implied by "dual system" views on self-control.